2009
DOI: 10.2334/josnusd.51.629
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength between an indirect composite veneering material and zirconia ceramics after thermocycling

Abstract: The present study evaluated the shear bond strength between an indirect composite material and zirconium dioxide (zirconia) ceramics after thermocycling. A total of 80 zirconia (Katana) discs were divided into five groups and primed with one of following agents: All Bond 2 Primer B (ABB), Alloy Primer (ALP), AZ Primer (AZP), Estenia Opaque Primer (EOP), and Porcelain Liner M Liquid A (PLA). An indirect composite material (Estenia C&B) was then bonded to the primed zirconia. One-half of the specimens (n = 8) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 3 publications
4
24
1
4
Order By: Relevance
“…However, combined adhesive failure and cohesive failure within the indirect composite material was observed in six groups that underwent thermocycling. These findings are consistent with those of a study (18) which noted that polymerization of Estenia composite material was still progressing at 37°C for 24 h and that thermal stress at 55°C with 20,000 thermocycles resulted in additional polymerization of the composite material.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, combined adhesive failure and cohesive failure within the indirect composite material was observed in six groups that underwent thermocycling. These findings are consistent with those of a study (18) which noted that polymerization of Estenia composite material was still progressing at 37°C for 24 h and that thermal stress at 55°C with 20,000 thermocycles resulted in additional polymerization of the composite material.…”
Section: Discussionsupporting
confidence: 82%
“…Two in vitro studies investigated short-term bond strength between an indirect composite used as veneering material and zirconia ceramics in zirconia-based restorations (17,18). Kobayashi et al (17) reported that application of priming agents containing MDP and an intermediate high-flow bonding agent resulted in superior bond strength between an indirect composite and zirconia ceramics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conflicting findings may be attributable to the bond strength between zirconia ceramics and indirect composite material. A previous study demonstrated that thermal cycling did not decrease bond strength between zirconia and indirect composite material, due to the ongoing polymerization of composite material with thermal stress at 55°C 29) . However, SEM observation of the current study suggests that surface treatment with primers has a positive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical roughening with a coarse diamond bur 12) , air-abrasion using alumina particles 13) , and chemical etching with hydrofluoric acid 14) have been shown to provide micromechanical interlocking at the ceramic-resin interface. Moreover, it has been reported that the applications of silane coupling agent and acidic functional monomer could produce chemical bonding to silica-based and zirconia ceramic materials [15][16][17] . 3-methacryloxypropyl trimethoxysilane (γ-MPTS) is widely used in adhesive dentistry as a silane coupler 18) .…”
Section: Introductionmentioning
confidence: 99%